Neutrophil-lymphocyte ratio and mean platelet volume can be a predictor for severity of acute appendicitis - UĞURLU, MUSTAFA ÜMİT; YEGEN, ŞEVKET CUMHUR (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2016)
BACKGROUND: Early diagnosis of perforation in acute appendicitis (AA) allows surgeons to select the most appropriate treatment. The aim of the present study was to determine whether preoperative neutrophil-lymphocyte ratio (NLR) and mean platelet volume (MPV) could predict perforation in AA. METHODS: Data collected from 413 consecutive patients with AA and 100 healthy controls were analyzed retrospectively. Patients were categorized as having had phlegmonous appendicitis, appendicitis with localized peritonitis, or appendicitis with perforation and/or gangrene. MPV and NLR values were compared among the control group and the 3 groups of patients with AA. RESULTS: Means values of MPV were 9.3 +/- 8 fL for the patient group and 8.5 +/- 0.9 fL for the healthy control group (p=0.0005). Mean values of MPV by patient subgroup were 8.8 +/- 5.8 for phlegmonous appendicitis, 8.9 +/- 5.8 for localized peritonitis, and 12.8 +/- 9.7 for appendicitis with perforation and/or gangrene (p= 0.005). Cut-off value of MPV was set at 8.92 to differentiate AA with perforation and/or gangrene from other types of AA. Mean NLRs of patients with phlegmonous appendicitis, appendicitis with localized peritonitis, and appendicitis with perforation and/or gangrene were 8.3 +/- 5.6, 9.1 +/- 6.2, and 10.6 +/- 6.4, respectively; p=0.023. The cut-off value for NLR was set at 7.95 to differentiate AA with perforation and/or gangrene from other types of AA. CONCLUSION: Both NLR and MPV can be useful in predicting severity of AA.
Keywords: Appendicitis; lymphocyte; mean platelet volume; neutrophil; predictive factors; C-REACTIVE PROTEIN; DIAGNOSIS; APPENDECTOMY; METAANALYSIS; INDICATOR; DISEASE; TRIAL; TESTS